Reduced Cortical Thickness in the Right Caudal Middle Frontal Is Associated With Symptom Severity in Betel Quid-Dependent Chewers - Sariah, Adellah; Pu, Weidan; Xue, Zhimin; Liu, Zhening; Huang, Xiaojun (Frontiers in Psychiatry, 2020)
Background: Findings from brain structural imaging studies on betel quid dependence have supported relations between betel quid chewing and alterations in gray matter volume and white matter integrity. However, the effect of betel quid chewing on cortical thickness, and the link between cortical thickness and symptom severity remains unascertained. Methods: In this observational study, we compared cortical thickness measures from 24 male betel quid-dependent chewers with 27 male healthy controls. Using FreeSufer, we obtained three-dimensional T1-weighted images that were used to compute the thickness of the cerebral cortex throughout the cortical layer. Results: Compared to healthy controls, betel quid dependent chewers displayed significant decreased cortical thickness in the precuneus, entorhinal, right paracentral, middle temporal, and caudal middle frontal gyri. Betel quid dependence scale scores negatively correlated (r = -0.604; p = 0.002) with reduced cortical thickness in the right caudal middle frontal of betel quid-dependent chewers. Conclusion: The findings provide evidence for cortical thickness abnormality in betel dependent chewers and further propose that the severity of betel quid symptoms may be a critical aspect associated with the cortical alterations. The observed alterations may serve as potential mechanisms to explain why BQ chewing behavior is persistent among individuals with betel quid dependence.